Chinese herbal medicine improves the treating outcomes in advanced non-small cell lung cancer patients treated with iodine-125 seed brachytherapy: a 5-year follow-up study - Li, Linjun; Zhang, Cheng; Luo, Jun; Zhou, Ruiqin; Zhou, Guoqing; Wu, Qingchen (Frontiers in Medicine, 2025)
Brachytherapy based on iodine-125 (I-125) is becoming one of the alternative treatment option for advanced non-small cell lung cancer (NSCLC). Chinese herbal medicine (CHM) combined with radiotherapy reduces the complications. In the current study, we attempted to assess the outcomes of treating strategies using CHM, chemotherapy or I-125. 182 patients who underwent I-125 seed implantation alone or in combination with chemotherapy or CHM treatment were enrolled in the current study. The clinical information of the patients were collected, and analyzed after a 5-year follow-up. The overall survival rates at 1, 2, 3, and 5 years were 81, 47, 28, and 20%, respectively, with a median survival time of 24.28 months. For patients receiving chemotherapy combined with I-125 seed brachytherapy, the survival rates were 89, 53, 35, and 29%, respectively. In contrast, those treated with CHM combined with I-125 seed brachytherapy had survival rates of 90, 63, 42, and 23%. Meanwhile, the survival rates for patients treated with 125I seed brachytherapy alone were 69, 32, 12, and 11%. Additionally, patients receiving CHM combined with I-125 seed brachytherapy treatment also showed less complications such as cough and vomit. CHM treatment demonstrated comparable efficacy and less complications to chemotherapy in managing advanced NSCLC under the treatment of I-125.